Percepcja przyrody w sonecie Stepy akermańskie Adama Mickiewicza i jego przekładach na język rosyjski - Borys, Iwona (Acta Polono-Ruthenica, 2018)
The paper analyses Russian translations of The Akkerman Steppes (Crimean Sonnets) from the perspective of perception of nature by the poet and its translations. The author examines their characteristics connected with the interpretation of this poem and the translation choice – a challenging exercise for translators.